Suberoylanilide hydroxamic acid, a histone deacetylase inhibitor, attenuates postoperative cognitive dysfunction in aging mice - Jia, Min; Liu, Wen-Xue; Sun, He-Liang; Chang, Yan-Qing; Yang, Jiao-Jiao; Ji, Mu-Huo; Yang, Jian-Jun; Feng, Chen-Zhuo (Frontiers in Molecular Neuroscience, 2015)
Postoperative cognitive dysfunction (POCD) is a recognized clinical entity characterized with cognitive deficits after anesthesia and surgery, especially in aged patients. Previous studies have shown that histone acetylation plays a key role in hippocampal synaptic plasticity and memory formation. However, its role in POCD remains to be determined. Here, we show that suberoylanilide hydroxamic acid (SAHA), a histone deacetylase inhibitor, attenuates POCD in aging Mice. After exposed to the laparotomy, a surgical procedure involving an incision into abdominal walls to examine the abdominal organs, 16- but not 3-month old male C57BL/6 mice developed obvious cognitive impairments in the test of long-term contextual fear conditioning. Intracerebroventricular (i.c.v.) injection of SAHA at the dose of (20 μg/2 μl) 3 hours before and daily after the laparotomy restored the laparotomy-induced reduction of hippocampal acetyl-H3 and acetyl-H4 levels and significantly attenuated the hippocampus-dependent long-term memory impairments in 16-month old mice. SAHA also reduced the expression of cleaved caspase-3, inducible nitric oxide synthase and N-methyl-D-aspartate receptor-calcium/calmodulin dependent kinase II pathway, and increased the expression of brain-derived neurotrophic factor, synapsin 1, and postsynaptic density 95. Taken together, our data suggest that the decrease of histone acetylation contributes to POCD and may serve as a target to improve the neurological outcome of POCD.